2009
DOI: 10.1186/1476-069x-8-25
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and emergency department visits for cardiac and respiratory conditions: a multi-city time-series analysis

Abstract: BackgroundRelatively few studies have been conducted of the association between air pollution and emergency department (ED) visits, and most of these have been based on a small number of visits, for a limited number of health conditions and pollutants, and only daily measures of exposure and response.MethodsA time-series analysis was conducted on nearly 400,000 ED visits to 14 hospitals in seven Canadian cities during the 1990s and early 2000s. Associations were examined between carbon monoxide (CO), nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
158
7
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 234 publications
(187 citation statements)
references
References 36 publications
17
158
7
5
Order By: Relevance
“…Of the 12 studies included in the metaanalysis (Figure 3), a positive association was found in 10; however, the association was significant in only 4. Studies in which researchers collected measurements of both PM 2.5 and PM 10 fractions, similar associations between COPD hospital admissions and these fractions were found (21,22,(26)(27)(28)(29)(30)(31). However, overall, a stronger association was found with PM 2.5 (OR, 1.03; 95% CI, 1.01-1.05) than with PM 10 , which might be explained by the fact that smaller particles may penetrate deeper into the lungs.…”
Section: Systematic Reviewmentioning
confidence: 66%
See 4 more Smart Citations
“…Of the 12 studies included in the metaanalysis (Figure 3), a positive association was found in 10; however, the association was significant in only 4. Studies in which researchers collected measurements of both PM 2.5 and PM 10 fractions, similar associations between COPD hospital admissions and these fractions were found (21,22,(26)(27)(28)(29)(30)(31). However, overall, a stronger association was found with PM 2.5 (OR, 1.03; 95% CI, 1.01-1.05) than with PM 10 , which might be explained by the fact that smaller particles may penetrate deeper into the lungs.…”
Section: Systematic Reviewmentioning
confidence: 66%
“…That approach has the potential for including a large number of days over several years for a large population, with advantages of improving the precision of estimate of effect of exposure-response relationships. The researchers in the vast majority of these studies analyzed exposureresponse relationships at a single-city level, and we found only six time-series multicity investigations (17)(18)(19)(20)(21)(22).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations